BIAYA PRODUKSI TEPUNG SAGU (Metroxylon sagu Rottb) SECARA SEMI MEKANIS PADA INDUSTRI USAHA KECIL DI DESA KOREK KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Bagaskara, Julio; Hardiansyah, Gusti; Setyawati, Dina (JURNAL HUTAN LESTARI, 2020)
Sago is a plant can be source of foods, and have a economic value. Production of sago flour need stages and experience. The purpose of this study is to describe the activity of sago flour production, analyze the cost, count revenue, and analyze advisability businesss sago flour production in Korek, Village of Sungai Ambawang, Sub-District of Kubu Raya Regency. This study uses survey method and interview technique. Production at Akos industry includes: supplying basic materials, stripping, splitting, rasping, filtering, precipitating, drying, milling, and packaging. The total costs of production at Akos industry is Rp 258.669,39/ hour, it is the sum of fixed costs and variable costs. Fixed costs are the cost of depreciation and capital interest is about Rp 3.717,47/ hour. Variable costs include the cost of basic materials, costs of transporting basic materials, employee salaries, fuel, packaging materials and delivery cost of raw materials is about Rp 254.951,92/ hour. Revenue of Akos industry is Rp 410.576,92/ hour gotten from selling sago flour class A is about 14 ton and selling sago flour class B is about 3 ton. Net income of Akos industry is Rp Rp 151.907,53/ hour. The based on the analysis, Akos industry has R/C value is 1,59. Because the value of R/C more than 1, so business of Akos flour sago industry is profitable, and advisable to be run.Keywords: Cost production, Diagram of sago flour production, R/C analysis